OC-030 Serum lipids and the risk of developing symptomatic gallstones: a UK prospective cohort study. (23rd September 2015) - Banim, P J R; Luben, R; Bulluck, H; Wareham, N J; Sharp, S; Khaw, K; Hart, A R
Abstract : Introduction: The formation of gallstones may be influenced by alcohol consumption, physical activity and obesity through their effects on serum lipids. The aim of this study was to investigate if the serum levels of cholesterol, triglycerides, high density lipoprotein-cholesterol (HDL) and low density lipoprotein-cholesterol (LDL) were associated with the risk of symptomatic gallstones, for the first time in a European prospective cohort study. Methods: A total of 21 850 men and women aged 45 to 74 years were recruited into the European Prospective Investigation into Cancer-Norfolk study between 1993 and 1997 and donated blood samples at enrolment. The cohort was then monitored over 14 years to identify participants who developed symptomatic gallstones, with each case reviewed by a physician to confirm the diagnoses. A cohort analysis was performed using Cox regression to estimate hazard ratios (HR) for developing symptomatic gallstones, in each gender, between quartiles of sex-specific serum lipid levels. In women, the HRs were adjusted for parity and hormone replacement therapy. Results: During follow-up, 179 women and 81 men developed symptomatic gallstones at a median age of 61.8 years (range 42.7–76.5 years) with most patients presenting with biliary colic. Serum HDL was negatively associated with gallstones in both genders. For men, the highest compared to the lowest quartile of HR=0.22 (95% CI 0.10 to 0.53, p for trend across quartiles=0.001) and for women the HR=0.52 (95% CI 0.33 to 0.81, p for trend=0.004). Serum triglycerides were positively associated with gallstone disease in women (highest compared to lowest quartile HR=2.36, 95% CI 1.48 to 3.77, p for trend<0.001). The equivalent results in men were of borderline significance (HR=1.84, 95% CI 0.94 to 3.60, p for trend=0.052). No effect was found for serum cholesterol and LDL. Conclusion: This study confirmed that raised serum triglycerides are associated with an increased risk of symptomatic gallstones whereas raised serum HDL is associated with a decreased risk. These findings provide plausible biological mechanisms for how alcohol, physical activity and obesity influence the development of gallstones. If the latter are altered in public health programmes then the incidence of gallstones could be significantly reduced.